Chaos of Rearrangements in the Mating-Type Chromosomes of the Anther-Smut Fungus Microbotryum lychnidis-dioicae. Issue 4 (3rd June 2015) - Badouin, Hélène; Hood, Michael E; Gouzy, Jérôme; Aguileta, Gabriela; Siguenza, Sophie; Perlin, Michael H; Cuomo, Christina A; Fairhead, Cécile; Branca, Antoine; Giraud, Tatiana
Abstract: Sex chromosomes in plants and animals and fungal mating-type chromosomes often show exceptional genome features, with extensive suppression of homologous recombination and cytological differentiation between members of the diploid chromosome pair. Despite strong interest in the genetics of these chromosomes, their large regions of suppressed recombination often are enriched in transposable elements and therefore can be challenging to assemble. Here we show that the latest improvements of the PacBio sequencing yield assembly of the whole genome of the anther-smut fungus, Microbotryum lychnidis-dioicae (the pathogenic fungus causing anther-smut disease of Silene latifolia ), into finished chromosomes or chromosome arms, even for the repeat-rich mating-type chromosomes and centromeres. Suppressed recombination of the mating-type chromosomes is revealed to span nearly 90% of their lengths, with extreme levels of rearrangements, transposable element accumulation, and differentiation between the two mating types. We observed no correlation between allelic divergence and physical position in the nonrecombining regions of the mating-type chromosomes. This may result from gene conversion or from rearrangements of ancient evolutionary strata, i.e., successive steps of suppressed recombination. Centromeres were found to be composed mainly of copia-like transposable elements and to possess specific minisatellite repeats identical between the different chromosomes. We also identified subtelomeric motifs. In addition, extensive signs of degeneration were detected in the nonrecombining regions in the form of transposable element accumulation and of hundreds of gene losses on each mating-type chromosome. Furthermore, our study highlights the potential of the latest breakthrough PacBio chemistry to resolve complex genome architectures.